The role and response of primary healthcare services in the delivery of palliative care in epidemics and pandemics: A rapid review to inform practice and service delivery during the COVID-19 pandemic. (October 2020) - Mitchell, Sarah; Maynard, Victoria; Lyons, Victoria; Jones, Nicholas; Gardiner, Clare
Background: The increased number of deaths in the community happening as a result of COVID-19 has caused primary healthcare services to change their traditional service delivery in a short timeframe. Services are quickly adapting to new challenges in the practical delivery of end-of-life care to patients in the community including through virtual consultations and in the provision of timely symptom control. Aim: To synthesise existing evidence related to the delivery of palliative and end-of-life care by primary healthcare professionals in epidemics and pandemics. Design: Rapid systematic review using modified systematic review methods, with narrative synthesis of the evidence. Data sources: Searches were carried out in Medline, Embase, PsychINFO, CINAHL and Web of Science on 7th March 2020. Results: Only five studies met the inclusion criteria, highlighting a striking lack of evidence base for the response of primary healthcare services in palliative care during epidemics and pandemics. All were observational studies. Findings were synthesised using a pandemic response framework according to 'systems' (community providers feeling disadvantaged in terms of receiving timely information and protocols), 'space' (recognised need for more care in the community), 'staff' (training needs and resilience) and 'stuff' (other aspects of managing care in pandemics including personal protective equipment, cleaning care settings and access to investigations). Conclusions: As the COVID-19 pandemic progresses, there is an urgent need for research to provide increased understanding of the role of primary care and community nursing services in palliative care, alongside hospices and community specialist palliative care providers.